Knuckle-walking and behavioural flexibility in great apes - Emily LR Tarrega-Saunders; Charlotte King; Alice M Roberts; Susannah KS Thorpe (Revue de Primatologie)
Kinematic differences in the knuckle-walking gaits of chimpanzees and gorillas have provided crucial evidence to support the theory that knuckle-walking evolved independently in the Pan and Gorilla lineages, rather than being inherited from their last common ancestor. This has been used to refute the idea that hominin bipedalism evolved from knuckle-walking. Extended wrist postures during knuckle-walking in chimpanzees compared with columnar wrist postures in gorillas were associated with chimpanzees’ more arboreal lifestyle, and are supposedly constrained by fundamental differences in carpal morphology. However, more recent kinematic data cast doubt on the presence of two distinct types of knuckle-walking in Pan and Gorilla. It is also becoming clear that primates demonstrate substantial flexibility in their locomotor ecology to adapt to habitat conditions, indicating that species-specific stereotyping of locomotion is inappropriate. Furthermore, the potential for plasticity in anatomical development presents challenges to evolutionary predictions that are based on tight links between skeletal form and locomotor function. Given the accumulating evidence showing substantial arboreality in gorillas, this study investigates wrist kinematics during both arboreal and terrestrial knuckle-walking in captive chimpanzees and gorillas, to address the hypothesis that previously reported kinematic differences are phylogenetically constrained, rather than merely a consequence of environment. We find that when the arboreal knuckle-walking behaviour of gorillas is considered, gorillas exhibit more extended wrist postures than chimpanzees, and are therefore capable of the same kinematic responses to arboreal supports. We propose that knuckle-walking epitomises a shared inheritance of behavioural flexibility in chimpanzees and gorillas, rather than either a shared inheritance of knuckle-walking itself or independent evolution of knuckle-walking in response to different environmental pressures. We suggest that future studies of hominoid locomotion consider a species’ full range of environmental contexts, as well as the potential influence of developmental plasticity on locomotor anatomy, in order to make more robust conclusions about the evolution of locomotor behaviour.